Development Of Foreign Language and Creative Thinking on Students of Higher Educational Institutions - Ochilova Nigora Normurodovna, (Academia One Publishing, 2024)
In this article, considerations and opinions on the development of foreign language and creative thinking among students of higher educational institutions are substantiated. The importantance of creative thinking for students is reflected in this article
Keywords: creative thinking; individual thoughts; beliefs